Infection of Monocytes From Tuberculosis Patients With Two Virulent Clinical Isolates of Mycobacterium tuberculosis Induces Alterations in Myeloid Effector Functions (2020)
ABSTRACT: Monocytes play a critical role during infection with Mycobacterium tuberculosis (Mtb). They are recruited to the lung, where they participate in the control of infection during active tuberculosis (TB). Alternatively, inflammatory monocytes may participate in inflammation or serve as niches for Mtb infection. Monocytes response to infection may vary depending on the particularities of the clinical isolate of Mtb from which they are infected. In this pilot study, we have examined the baseline mRNA profiles of circulating human monocytes from patients with active TB (MoTB) compared with monocytes from healthy individuals (MoCT). Circulating MoTB displayed a pro-inflammatory transcriptome characterized by increased gene expression of genes associated with cytokines, monocytopoiesis, and down-regulation of MHC class II gene expression. In response to in vitro infection with two clinical isolates of the LAM family of Mtb (UT127 and UT205), MoTB displayed an attenuated inflammatory mRNA profile associated with down-regulation the TREM1 signaling pathway. Furthermore, the gene expression signature induced by Mtb UT205 clinical strain was characterized by the enrichment of genes in pathways and biological processes mainly associated with a signature of IFN-inducible genes and the inhibition of cell death mechanisms compared to MoTB-127, which could favor the establishment and survival of Mtb within the monocytes. These results suggest that circulating MoTB have an altered transcriptome that upon infection with Mtb may help to maintain chronic inflammation and infection. Moreover, this functional abnormality of monocytes may also depend on potential differences in virulence of circulating clinical strains of Mtb.